2001
DOI: 10.7589/0090-3558-37.1.28
|View full text |Cite
|
Sign up to set email alerts
|

Interspecific Variability of Prevalence in Blood Parasites of Adult Passerine Birds During the Breeding Season in Alaska

Abstract: Blood parasite prevalence based on microscopic examination of stained blood smears was determined in adults of 11 passerine bird species sampled during their breeding season (May and June 1997-98) in interior Alaska (USA). These species included primarily Nearctic migratory species such as the dark-eyed junco (Junco hyemalis) and neotropical migratory species such as the blackpoll warbler (Dendroica striata), alder flycatcher (Empidonax alnorum), Swainson's thrush (Catharus ustulatus), northern waterthrush (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
36
2
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 28 publications
0
36
2
1
Order By: Relevance
“…This might explain the observation of clinical signs in infected birds, since it seems reasonable to assume that the higher the number of parasites the more pathogenic is their action. The 1.3 % incidence reported here is low if compared with studies from areas at higher latitudes (Rintamaki et al, 1999 ;Deviche et al, 2001 ;Holstad et al, 2003), taking also into account that the population examined includes 921 'diseased' falcons and not one healthy falcon. However, results from studies carried out on freeranging falcons admitted to wildlife rescue centres, accordingly to be considered 'diseased', are overlapping.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…This might explain the observation of clinical signs in infected birds, since it seems reasonable to assume that the higher the number of parasites the more pathogenic is their action. The 1.3 % incidence reported here is low if compared with studies from areas at higher latitudes (Rintamaki et al, 1999 ;Deviche et al, 2001 ;Holstad et al, 2003), taking also into account that the population examined includes 921 'diseased' falcons and not one healthy falcon. However, results from studies carried out on freeranging falcons admitted to wildlife rescue centres, accordingly to be considered 'diseased', are overlapping.…”
Section: Discussioncontrasting
confidence: 71%
“…This assumption does not seem to be based on verifiable facts but on the lack of direct research, since today only morphological (Yurchenko et al, 1999) and epidemiological informations (Kirkpatrick & Lauer, 1985 ;Munoz et al, 1999) are available. Most of previous studies were carried out on wild animals captured and released after sampling (Rintamaki et al, 1999;Deviche et al, 2001;Holstad et al, 2003 pathogenic effects are easier to detect and to describe. This seems to be the first attempt to study clinical signs and the response to therapy of T. avium infection in captive birds of prey.…”
Section: Discussionmentioning
confidence: 99%
“…Both intra-and interspecific variation in the prevalence of blood parasites is well documented (Merilä et al 1995), and factors contributing to this variation are quite varied (Deviche et al 2001). It was not clear why the prevalence of hematozoan infections among Rusty Blackbirds in Alaska (44%) is less than half that reported from Newfoundland (100%; ) and intermediate in Maine (67%).…”
Section: Discussionmentioning
confidence: 98%
“…ranged from 20 to 32 %. The prevalence of blood parasite in pigeons and birds in Japan (Murata 2002), Costa Rica (Valkiunas et al 2004) and Alaska (Deviche et al 2001) was shown to be lower than 10 %. H. columbae infects pigeons which are associated with human settlements.…”
Section: Discussionmentioning
confidence: 99%